The Role Of The Prosecutor's Office In Rescuing State/Regional Assets As An Effort To Prevent Corruption In Indonesia - Ricky Setiawan Anas; Ahmad Redi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The recovery of state/regional assets is one of the important strategies in preventing corruption in Indonesia. The AGO, as a law enforcement agency, has a central role in restoring state assets suspected of being the proceeds of corruption. However, in practice, the AGO faces various obstacles that affect the effectiveness of asset recovery. Legal constraints such as overlapping regulations, complicated procedures, and asset ownership, are core difficulties. In addition, limited human resources and technology, as well as socio-political factors involving corruption in government institutions, also worsen the asset recovery process. This research focuses on identifying and analyzing the obstacles faced by the AGO in recovering state and regional assets. It also aims to outline the necessary steps to enhance the AGO's effectiveness in preventing corruption.